2011
DOI: 10.1063/1.3599485
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of carrier mobility in organic field-effect transistors

Abstract: Temperature-dependent carrier mobility and threshold voltage of field-effect transistors with tetracene single crystals Influence of interface modifications on carrier mobilities in rubrene single crystal ambipolar field-effect transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…d) Calculated mobility for this OFET versus gate voltage and temperature. Adapted with permission . Copyright 2011, AIP.…”
Section: Bias Dependencesmentioning
confidence: 99%
“…d) Calculated mobility for this OFET versus gate voltage and temperature. Adapted with permission . Copyright 2011, AIP.…”
Section: Bias Dependencesmentioning
confidence: 99%
“…For such devices, λ can be of the same order as the semiconductor thickness t sc and the charge carriers accu-mulate almost uniformly throughout the semiconductor. In this situation, the charge transport in the subthreshold region is essentially a volume phenomenon rather than an accumulation of charge carriers within the first few monolayers of the semiconductor 32 .…”
Section: Subthreshold Swing and Trap Densitymentioning
confidence: 99%
“…[51,52] Liu et al observed a dielectric-dependent R C in OTFTs that were made with the same OSC, and suggested that the reason for this dependency on the dielectric was that different amounts of charge carriers were trapped at the OSC/dielectric interface as they were injected into the channel. [26,53,54] Additionally, others have shown that interfacial layers can be used to reduce charge trapping at the OSC/dielectric interface which in turn reduces R C . [26,53,54] Additionally, others have shown that interfacial layers can be used to reduce charge trapping at the OSC/dielectric interface which in turn reduces R C .…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%